Dialog dan Kerjasama Antar Umat Beragama dalam Perspektif Nurcholish Madjid - Zaprulkhan Zaprulkhan (Faculty of Da’wa and Islamic Communication, State Institute for Islamic Studies of Syaikh Abdurrahman Siddik Bangka Belitung, 2018)
When leaving the end of the second millennium and entering the beginning of the third millennium, humankind is faced with the phenomenon of conflict in the name of religion, both on a regional and global level. In modern history, there are so many conflicts that occur in the name of beliefs in different parts of the world. In the context of Indonesia, both of impacts of various conflicts and conflicts between various beliefs are rising to the surface ahead of the beginning of the third millennium to the present day. All this requires dialogue and open cooperation between religious communities. In the context of Indonesia, in order to contribute maximally to the good, and the progress of the nation and state, all religious people must be willing to engage in dialogue and cooperation in the social, cultural, economic, political, human quality of Indonesia and others. Therefore, we will explore the discourse of dialogue and cooperation among religious people in the perspective of Nurcholish Madjid.